2015
DOI: 10.1186/s13104-015-1532-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of gingivitis in school students aged 6–11 years in Tafelah Governorate, South Jordan: results of the survey executed by National Woman’s Health Care Center

Abstract: BackgroundA cross-sectional census was conducted on 994 public school students aged 6-11 years living in 3 different parts of Tafeleh Governorate—South of Jordan, to determine the prevalence, and severity of gingivitis and to evaluate the oral hygiene habits among them as a part a survey executed by National Woman’s Health Care Center. All students were examined for gingival index (GI) and plaque index (PI), information about oral hygiene habits was recorded.ResultsOnly 29.8 % had healthy gingiva, 38.5 % had m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
(25 reference statements)
5
14
3
Order By: Relevance
“…18 On the other hand, international epidemiological studies have shown great variation in the prevalence of gingivitis in children and adolescents, with figures ranging from 14.5% to 70.2%. 19,20 These data agree with the figures obtained in this study, 36.8% for the 2-year-old children and 70.5% for the 4-year-olds. In contrast, a study conducted in the city of Temuco reported a higher prevalence of gingivitis: 93.1% at 4 years of age.…”
Section: Discussionsupporting
confidence: 91%
“…18 On the other hand, international epidemiological studies have shown great variation in the prevalence of gingivitis in children and adolescents, with figures ranging from 14.5% to 70.2%. 19,20 These data agree with the figures obtained in this study, 36.8% for the 2-year-old children and 70.5% for the 4-year-olds. In contrast, a study conducted in the city of Temuco reported a higher prevalence of gingivitis: 93.1% at 4 years of age.…”
Section: Discussionsupporting
confidence: 91%
“…This descriptive and cross-sectional study has made it possible to determine the prevalence of gingivitis in children consulted at the Bamako Dental Center in Mali. The prevalence of gengivitis was 87.5% and this result is comparable to observed in Southern Jordan (70.2%) [6], and in Puerto…”
Section: Discussionsupporting
confidence: 77%
“…However, a study on 15‐year‐old children in Latvia reported 40.6% gingival BOP in boys compared to 37.4% in girls . Another study failed to observe any significant sex difference in 6‐11‐year‐old children of Tafelah Governorate in South Jordan . In the present study, 56.1% of boys compared to 52.1% of girls had gingival BOP (Table ), which could be attributed to 47.8% of boys cleaning the teeth twice a day or more compared to 52% of girls (Table ).…”
Section: Discussioncontrasting
confidence: 76%
“…Additionally, in the present study, we observed that 46.1% of children with a lower SES had never visited a dentist compared to 26.2% with an upper SES (Table ). Literature varies widely in this regard, with reports of 76% of 12 year olds in Tanzania and 85.9% of the examined 6‐11 year old school children of Tafelah in Jordan never having visited a dentist. Regular dental visits are essential for better oral health, and the upper strata have access to, and can afford, dental care.…”
Section: Discussionmentioning
confidence: 99%